Performance and ingestive behavior of Holstein and Girolando heifers grazing temperate forages - Abreu, Marcelo de Barros (2019)
This study aimed to investigate the difference between Holstein and Holstein x Gyr breeds on performance and ingestive behavior of dairy heifers grazing an intensively managed temperate pasture. The experiment was conducted during 89 days, divided into 14 days for adaptation plus three periods of 25 days. The heifers were divided into two treatments: Holstein (HOL. n = 7) with body weight (BW) of 235 ± 31.7 kg and Holstein × Gyr (HG. n = 7) with BW of 247 ± 34.0 kg. All heifers grazed 1.5 ha divided into 25 paddocks (577 m 2 ) of ryegrass (Lolium multiflorum Scherb) and Bristle Oats (Avena strigose Lam) consortium. Heifers were supplemented individually daily with corn meal at 0,33% of BW plus 5 kg/d of corn silage as partial mixed ration (PMR). From d 13 to 15 of each period, the evaluation of ingestive behavior was performed. The digestibility trial was done between days 16 and 24 of each period. The body measurements were taken and heifers were weighed at d 0 and at days 23, 24, and 25 of each period. At experimental days 0 and 75, an ultrasound device was used to measure carcass parameters. Blood samples were collected on d 25 of each period. At the end of the experimental period, ruminal fluid samples were obtained using an esophagic tube. Data were analysed as a completely randomized design and period was added, when necessary, as a repeated measured to the model. The grazing duration (130.73 vs 179.70), and grazing criteria (32.74 vs 59.58) were greater for HG heifers. HOL heifers had greater grazing frequency (8.03 vs 7.71), and greater bite rate (min/d) (20.01 vs 17.30) than HG heifers. Rumination characteristics were not affected by breed. The ADG was not affected by breed (1.03 kg/d for HOL and 1.17 kg/d for HG). HOL and HG heifers had similar intake and digestibility responses. The body measurements, carcass, blood, rumen, and nitrogen parameters were also not affected by the breed. Although breeds had slight differences in ingestive behavior, primarily in grazing characteristics, these effects did not affect performance or intake parameters. Therefore, HOL and HG replacement heifers managed under temperate pasture in tropical countries have adequate and similar performance.